Study of Formulation and Evaluation of the Potential Inhibitory Power of Basil Leaf Extract Hand Sanitizer Gel (Ocimum Sanctum L.) Against Staphylococcus Aureus: Literature Review - Melinda, Nailus Amany; Safitri, Putri Gita Ayu; Laili, Fauza Nisfu; Himmah, Siti Ro'yatul (Jurnal Surya, 2022)
Introduction: The basil plant (Ocimum sanctum) has the potential to be developed into antibacterial due to the content of tannin compounds, flavonoids, and essential oils. Antibacterial is a compound produced by microorganisms so that it can inhibit the growth of bacteria and kill bacteria that cause infection. The number of side effects so that many antibacterial developments are carried out derived from natural ingredients. The development of formulas for hand sanitizer gel preparations has been widely developed, including with various studies using various concentrations of basil leaf extract. This study was conducted to determine the gel formula for hand sanitizer ethanol extract of basil leaves (Ocinum Sanctum L.) which has the best inhibition against Staphylococcus bacteria.Methods: Review literature is obtained from several journal libraries, journal searches, and trusted sites.Results: There are 14 journals as a library, which display results from antibacterial gel preparation formulations, bacterial inhibitory testing and evaluation testing of basil leaves. The results of the review showed that basil leaves (Ocimum sanctum L.) have antibacterial activity against Staphylococcus aureus bacteria.Conclusion: The best hand sanitizer gel formula was in a study conducted with a concentration of 8% basil leaf extract with an inhibitory power of 12.0 ± 3.10 mm which was included in the category of strong inhibitory power.